Customer Satisfaction on E-commerce Logistics Distribution Service Quality: A Case Study of Jingdong - Dong, Wenqiang; Chamchang, Panida (Science, Technology, and Social Sciences Procedia, 2021)
This paper studies the satisfaction theory. Based on the China Satisfaction Index Model (CCSI) that meets China’s national conditions and previous studies, the CCSI is improved according to the characteristics of e-commerce companies, and 5 dimensions are determined, namely Enterprise contact, perceived service quality, communication and convenience quality, service price and expected quality, build a customer satisfaction model for e-commerce logistics and distribution services. Based on these 5 dimensions, 21 evaluation index systems for e-commerce logistics and distribution services based on customer perception have been constructed. A questionnaire was designed, and SPSS software was used to test the reliability and validity of the scale through empirical research, and the structural equation model was used to conduct empirical research with Jingdong e-commerce logistics as an example. The empirical results showed that the perceived service quality and the quality of communication and convenience The effects of customer satisfaction coexist, and both have a greater impact on customer satisfaction. Improving the quality of e-commerce logistics and distribution services should focus on these 2 aspects. And it provides reasonable countermeasures and suggestions.